2018
DOI: 10.1080/14660970.2018.1432385
|View full text |Cite
|
Sign up to set email alerts
|

The nature and function of talent identification in junior-elite football in English category one academies

Abstract: The focus of this study was to examine the nature and function of talent identification in category one football academies in the UK. Data were collected from three participant groups: heads of recruitment (n=12), recruitment staff (n=18), and scouts (n=7). Data were collected by means of semi-structured interviews, conducted either face-to-face or via Skype®. Four themes emerged from the data: 1) league structures in junior grassroots football; 2) reflective practice; 3) looking at the whole player; and 4) lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…Interestingly, the recruitment philosophy was visible in the interview room–a vinyl graphic occupying approximately two-thirds of a wall–when Adam and Ben were asked how accurate their thoughts and observations were in relation to this, they responded by further disagreeing with their previous verbalisations and aligning their responses to factors highlighted in the vinyl graphic. Such dissonance between philosophies and on-the-ground practice have been reported in previous studies [12, 14].…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…Interestingly, the recruitment philosophy was visible in the interview room–a vinyl graphic occupying approximately two-thirds of a wall–when Adam and Ben were asked how accurate their thoughts and observations were in relation to this, they responded by further disagreeing with their previous verbalisations and aligning their responses to factors highlighted in the vinyl graphic. Such dissonance between philosophies and on-the-ground practice have been reported in previous studies [12, 14].…”
Section: Resultssupporting
confidence: 72%
“…Talent scouts act as the on-the-ground face of the clubs that they represent; they are the individuals who often make first contact with potentially talented players. Whilst their primary function is to identify players and pass on information to full-time recruitment staff, they regularly continue to communicate with players and their family during and after a trial period with the club may have taken place [12]. Talent scouts, therefore, play an important role in the decision-making process regarding the players that are recruited to a club; they observe, capture data, and employ subjective judgements based on on-field actions [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also suggested that RAE bias could exist due to social factors, such as an earlier engagement in sporting activities or (un)conscious judgments by coaches influenced by physical factors related to growth and maturation ( Hancock et al, 2013 ; Wattie et al, 2014 ). Although progress in understanding and communicating the RAE has been made over recent years, the “win now” emphasis encompassing youth sport remains, particularly within soccer ( Andronikos et al, 2016 ; Reeves et al, 2018a ; Hill et al, 2019 ; Lupo et al, 2019 ; Jackson and Comber, 2020 ). This demand for immediate success has resulted in a maturation-selection phenomenon, whereby chronologically older players are preferred due to their superior physical qualities ( Lovell et al, 2015 ; Johnson et al, 2017 ; Hill et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%